Self-enforcing capital tax coordination - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2013)
Capital tax competition is known to result in inefficiently low tax rates and an undersupply of public goods. The provision of public goods and with it the welfare of all countries can be enhanced via tax coordination. Based on the standard Zodrow-Mieszkowski-Wilson tax-competition model this paper analyses the conditions under which tax coordination by a group of countries is self-enforcing. It is shown that there always exists a rather small stable tax coalition. For some subset of the parameter space the grand coalition may be stable as well, even if the total number of countries is large. The small stable coalition is not very effec- tive in mitigating the inefficiency of the non-cooperative Nash equilibrium. The ineffectiveness is increasing in the total number of countries.
Keywords: C72; H70; H73; 330; tax coordination; tax competition; coalition; self-enforcing